Hybrid System Prototype for Dam Water Level Control System to Irrigating Rice Fields - Hidayat, Agung Wahyu; Sulistiyowati, Indah; Wicaksono, Arief; Syahrorini, Syamsudduha (Buletin Ilmiah Sarjana Teknik Elektro, 2024)
Naturally, one of the causes of crop failure in agriculture is flooding brought on by unchecked water overflow, particularly during the rainy season. Crop failure is a common source of complaints from farmers because, in addition to making it harder for them to sell their harvests, it decreases the price at which rice is sold to customers, which reduces the amount of people who purchase rice. This project aims to develop a hybrid dam water level control system prototype for paddy field irrigation. In this instance, the innovative flood monitoring and control system integrates Blynk as a user interface that can be accessible via software, along with an ESP 32 monitoring unit and a NodeMCU 8266 controller. like smartphone devices. The ESP 32 controls servo motor 1 to open the dam door in the event of flooding. In addition, the ESP 32 monitors the dam's water level using the I2C LCD and alerts the user with a bell. The NodeMCU 8266 functions as a link to the ultrasonic sensor to relay the water level data to the ESP 32. Through the Blynk application, the user can manually control Servo motor 2 to open and close the dam door with configurable water level limitations. The results of the studies indicate that this system functions flawlessly, from setting up a warning system to connecting tools. The system may be manually operated by making use of microcontroller technology.